Single-molecule detection on a protein-array assay platform for the exposure of a tuberculosis antigen - Schmidt, Ronny; Jacak, Jaroslaw; Schirwitz, Christopher; Stadler, Volker; Michel, Gerd; Marmé, Nicole; Schütz, Gerhard J.; Hoheisel, Jörg D.; Knemeyer, Jens-Peter (Journal of proteome research, 2011)
Based on a single-molecule sensitive fluorescence-linked immunosorbent assay, an analytical platform for the detection of lipoarabinomannan (LAM), a lipopolysaccharide marker of tuberculosis, was established that is about 3 orders of magnitude more sensitive than comparable current ELISA assays. No amplification step was required. Also, no particular sample preparation had to be done. Since individual binding events are detected, true quantification was possible simply by counting individual signals. Utilizing a total internal reflection configuration, unprocessed biological samples (human urine and plasma) to which LAM was added could be analyzed without the requirement of sample purification or washing steps during analysis. Samples containing about 600 antigen molecules per microliter produced a distinct signal. The methodology developed can be employed for any set of target molecules for which appropriate antibodies exist.
Gesehen am 13.10.2022